Outcomes and Predictors of Mortality for Patients with Acute Leukemia Admitted to the Intensive Care Unit. (30th June 2016) - Kraguljac, Alan P.; Croucher, Danielle; Christian, Michael; Ibrahimova, Narmin; Kumar, Vikram; Jacob, Gabriella; Kiss, Alex; Minden, Mark D.; Mehta, Sangeeta
Abstract : Purpose . The objectives were to describe the management and outcomes of acute leukemia (AL) patients admitted to the ICU and to identify predictors of ICU mortality. Methods . Data was retrospectively collected from the medical records of all patients with AML or ALL admitted to the Mount Sinai Hospital ICU from August 2009 to December 2012. Results . 151 AL patients (117 AML, 34 ALL) were admitted to the ICU. Mean age was 54 (SD 15) years, median APACHE II score was 27 (IQR 22–33), and 50% were female. While in ICU, 128 (85%) patients had sepsis and 56 (37%) had ARDS. The majority of patients required invasive organ support: 94 (62%) required mechanical ventilation while 23 (15%) received renal replacement therapy. Multivariable analysis identified SOFA score (OR 1.18, 95% CI 1.01–1.38) and invasive ventilation (OR 9.64, 95% CI 3.39–27.4) as independent predictors of ICU mortality. Ninety-four (62%) patients survived to ICU discharge. Only 39% of these 94 patients discharged were alive 12 months after ICU admission. Conclusions . AL patients admitted to the ICU had a 62% ICU survival rate; yet only 25% of cohort patients were alive 12 months after ICU admission. Higher admission SOFA scores and invasive ventilation are independently associated with a greater risk of dying in the ICU.